1980
DOI: 10.1017/s0031182000061990
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the sites of acid phosphatase activity in an adult filaria, Setaria sp. and in some gastro -intestinal nematodes

Abstract: SUMMARYThe histochemical localization of acid phosphatase in an adult filaria, Setaria sp. obtained from the peritoneal cavity of a cow was closely examined and compared with that of adult nematodes parasitic in the host alimentary canal; special attention was paid to the intestine and body wall of the parasites. Setaria sp. was found to show high acid phosphatase activity in the interchordal hypodermis of the body wall and uterine microfilariae, and similar activity is suspected to occur in the cuticle. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Acid phosphatase has been demonstrated in this region of the hypodermis. In other nematodes this enzyme is only present in the intestinal epithelium (Maki and Yanagisawa 1980;Howells and Chen 1981). Furthermore, Omar et al (1993) found non-speci®c esterases in the hypodermis of O. fasciata, which are probably involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Acid phosphatase has been demonstrated in this region of the hypodermis. In other nematodes this enzyme is only present in the intestinal epithelium (Maki and Yanagisawa 1980;Howells and Chen 1981). Furthermore, Omar et al (1993) found non-speci®c esterases in the hypodermis of O. fasciata, which are probably involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%